Muhammadiyah dan NU dalam Kanvas Sejarah Dua Sayap Modernitas Islam Indonesia - Zahratunnisa Zahratunnisa; Azmi Endah; Nanda Luvia (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Muhammadiyah and Nahdlatul Ulama (NU) are the two largest Islamic organizations in Indonesia that form the “two wings” of modernity in Islam Nusantara. Muhammadiyah, founded by KH Ahmad Dahlan in 1912, emphasizes the purification of teachings through modern education, Health, and urban da’wah. NU, born in 1926 under KH Hasyim Asy’ari, preserved the pesantren tradition while adapting to colonialism. Both became the canvas of the history of the Islamic movement from independence to the 1998 Reformation, combining reform and conservation. This study aims to analyze their dialectical role in building an inclusive, tolerant, and progressive Islamic identity amidst socio-political dynamics. Analytical and descriptive qualitative methods were applied, analyzing journals related to Muhammadiyah and Nahdlatul Ulama. Key findings: Muhammadiyah modernized urban areas through thousands of schools and hospitals; NU strengthened rural areas through Kyai and pesantren. Collaboration was evident in the 1945 Jakarta Charter and the 1984 Congress, producing moderate Islam that rejects radicalism, contributing 60% of national political cadres post-New Order. Both create harmony between reform and tradition: Recommendations to strengthen dialogue between factions in the face of contemporary digitalization of da’wah. Keywords: Muhammadiyah, Islamic Modernization, NU